A határmenti fekvés szerepe a falusi települések életében - Kovács, Teréz (Tér és Társadalom, 1991)
In the Centre for Regional Studies of the Hungarian Academy of Sciences an overall research project started in 1986 on frontier location. Until now, the issue of frontier location has almost exclusively been dealt with the geographers. The present study intends to approach this problem from sociological aspects, thus it fills a gap. In contrast to geographers, who speak about frontier location as an (economic) periphery, the author emphasizes that these were not the regions located near the frontier which became peripheries, but the whole region became part of the empire region (according to Wallerstein’s expression). The charasteristic of a "modern empire" (strong central management and control, negligence of national features) were charasteristic of Hungary’s economic and social conditions between 1947 and 1989, and it hindered the development of settlements located near the frontier location itself. Frontier location might have secondary or tertiary, but definitely not primary role in the backwardness of rural areas. Population decrease, charasteristic of all the backwarded areas of the country, and can be related to those socio-economic tendencies and settlement policies, which existed in Hungary from the 1960s. The inhabitants of villages located near the frontier do not feal it either, that the reasons of the backwardness of their settlement should be found in frontier location. These people are realistic, and the lack of jobs and cities are everyday problems for them; more precisely they know that the latter are "far away" from them. The reasons of the unfavourable development of villages located near the frontier were the following: bad infrastructural supply and poor transportation facilities, unfavourable natural conditions, the lack of the tradition of individual entrepreneurship and their accumulation. The study mentions, that between 1920 and 1937, Hungary belonged to the periphery as Wallerstein means it, and at that time, the frontier was not strict, people could cross it practically freely. The most open was the Austro-Hungarian frontier. At that part, people crossed the the frontier not only in order to participate at the regular weekly markets, but the Hungarian went to Austria for daywork, because they were paid better. However, the Austrian bricklayers came over to Hungary to build houses, because they were acknowledged masters. The dayworkers of the villages located near the frontier met a more developed labour culture and used better tools, and they introduced them in Hungary as well. The Hungarian students of Burgenland came to study at the secondary school of Sopron and Kőszeg. Earlier connections and relationship, however, could not be sustained between the regions inhabited by Hungarians on both sides of the frontier. The reason was, that the neighbouring countries feared reannexation much more at these parts, than at the parts where the artificial frontier was the same as the national one. In the era called "modern empiricism" in the study, the conditions to establish relatives were not given. Whatever relations and connections did develop, they did it spontaneously, without the control, or often enough in spite of the intentions, of the central organizations. The changes which started to take place in Eastern-Europe in 1989 let us conclude, that the frontiers will become less rigid, and we are right before the development of many-sided relationship. Hopefully, this will result in an ideal state when frontiers are only lines on the map.